AKSELERASI IMPLEMENTASI KURIKULUM TINGKAT SATUAN PENDIDIKAN (KTSP) DALAM PEMBELAJARAN - Rustam Abong (AT-TURATS, 2008)
Educational Unit Level Curriculum (KTSP) is the operational curriculum designed by and implemented in each educational unit. While central government provides only rules of the standard course content, the technical drafting is assigned to teachers, principals and other related institutions. Therefore, accelerating the implementation KTSP in learning must be designed interactively, and the application should be in a way "to design learning to competence". To be directed to the competence of learning, teachers should design syllabus, Learning Implementation Plan (RPP), and Student Worksheet (BLM). In Addition, teachers, in the implementation of the learning are expected to help relate the teaching material to the real situations and encourage students to make connections between the knowledge learn and the application in their everyday life by using strategies of Contextual Teaching and Learning (CTL).